Effect of curing condition on the characteristics of mortar containing high volume supplementary cementitious materials / Evi Aprianti S - Evi , Aprianti S (2017)

(untitled)
The purposes of this research were to studies the physical and chemical properties of materials, compressive strength, flexural strength, water absorption and porosity of multi-blended cements under different curing methods. Due to an enormous amount of different types of waste materials as by-product from different sectors like industrial and agricultural produced globally but not deposited safely. One solution to this crisis lies in recycling waste into useful products. Fly ash (FA), palm oil fuel ash (POFA), ground granulated Blast furnace slag (GGBFS) and rice husk ash (RHA) were used to replace with 50% to 75% ordinary Portland cement (OPC) by mass. Specimens were cured in water (WC), air under room temperature (AC), the combination of hot-water at 60oC for 24 h followed by curing in water (HWC), and air (HAC). The results showed that HAC could be an effective curing method with higher compressive and flexural strengths, lower water absorption and porosity for blended cement mortars. Mortars containing GGBFS in binder had higher enhancement on compressive strength under early hot water curing. While, at 24 h hot water curing mortar containing OPC-RHA-FA binder showed better quality in properties compared to the other binders.